2019
DOI: 10.1002/jum.15190
|View full text |Cite
|
Sign up to set email alerts
|

Can Accurate Shear Wave Velocities Be Obtained in Kidneys?

Abstract: Objectives There are conflicting results in the literature on the use of shear wave elastography of the kidney parenchyma to determine whether renal stiffness values are related to a disease process. This study was conducted to evaluate the raw data from 3 ultrasound systems and determine whether adequate displacement curves are obtained to accurately estimate shear wave speeds. Methods Shear wave elastography was performed on 5 healthy volunteers with 3 ultrasound systems. The raw data were collected and eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 30 publications
(42 reference statements)
0
13
0
Order By: Relevance
“…The kidney represents an apt example. Multiple articles have been published regarding the investigation of the normal and abnormal kidney by this technique, which resulted in conflicting results regarding its clinical usefulness and reproducibility 22 , 31 . Currently, some authors question if any of the literature on renal shear wave elastography is accurate 22 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The kidney represents an apt example. Multiple articles have been published regarding the investigation of the normal and abnormal kidney by this technique, which resulted in conflicting results regarding its clinical usefulness and reproducibility 22 , 31 . Currently, some authors question if any of the literature on renal shear wave elastography is accurate 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Multiple articles have been published regarding the investigation of the normal and abnormal kidney by this technique, which resulted in conflicting results regarding its clinical usefulness and reproducibility 22 , 31 . Currently, some authors question if any of the literature on renal shear wave elastography is accurate 22 . Unique shear wave generation pulsing technology with specific processing algorithms adapted to the kidney are being developed, and may be able to overcome the issue of SWS variability 22 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study [65] evaluating the raw data from renal SWE demonstrated that accurate SWS estimates could not be obtained from most vendors systems. The displacement curves were evaluated from several manufactures to determine if accurate shear wave speeds could be estimated in the kidney, both cortex and medulla.…”
Section: Main Objectives Clinical Valuementioning
confidence: 99%